उर्दू-हिन्दी परिचय कोश - Sitaram Shastri (Kendriya Hindi Sansthan, Agra, 2003)
This is an introductory dictionary for vocabulary building.
Urdu-Hindi Parichay Kosh
Keywords: उर्दू-हिन्दी परिचय कोश; Urdu; Dictionary; Urdu; Urdu; Hindi